2020
DOI: 10.1007/s12975-020-00781-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Angiographic Hemodynamic Evaluation After Revascularization Surgery for Moyamoya Disease

Abstract: The corresponding hemodynamic changes of the internal carotid artery (ICA) after the revascularization surgery for moyamoya disease (MMD) remain unclear. The aim of this study was to analyze the hemodynamic changes of the ipsilateral ICA after the combined direct and indirect extracranial-intracranial (EC-IC) bypass. MMD patients undergoing combined EC-IC bypass were retrospectively reviewed. The mean transit time (MTT) of ICA was evaluated by color-coding angiography before revascularization and at follow-up.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 52 publications
1
16
1
Order By: Relevance
“…A previous study revealed that the presence of the brush sign was significantly associated with a poor outcome in patients with ischemic stroke [ 25 ]. With UHF MRI, the conspicuity of deep medullary vein increased, which enabled it to sensitively anticipate the extent of the impaired perfusion in MMD without the need to perform hemodynamic examinations, such as CTP, ASL, SPECT, or PET [ 26 , 27 ]. The application of the SWI sequence in high-field MRI in the assessment of hemodynamics of patients with MMD still needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that the presence of the brush sign was significantly associated with a poor outcome in patients with ischemic stroke [ 25 ]. With UHF MRI, the conspicuity of deep medullary vein increased, which enabled it to sensitively anticipate the extent of the impaired perfusion in MMD without the need to perform hemodynamic examinations, such as CTP, ASL, SPECT, or PET [ 26 , 27 ]. The application of the SWI sequence in high-field MRI in the assessment of hemodynamics of patients with MMD still needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Dilated AChA-PCoA was reported to be present in 41.7–71.9% of hemorrhagic MMD patients [ 16 , 35 , 36 , 37 ], and 23.2–70.1% of them would be improved after revascularization [ 27 , 34 , 38 ]. This change in vascular remodeling may be related to ipsilateral ICA disuse occlusion caused by extracranial-intracranial (EC-IC) blood flow conversion after revascularization [ 39 , 40 ]. In this study, 80.3% of patients observed improvement in dilated AChA-PCoA after direct revascularization, and the improvement of dilated AChA-PCoA has no significant correlation with graft patency.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 80.3% of patients observed improvement in dilated AChA-PCoA after direct revascularization, and the improvement of dilated AChA-PCoA has no significant correlation with graft patency. Neoangiogenesis was recognized as the most intuitive angiographic prognostic indicator after revascularization in MMD patients [ 19 , 39 ]. Previous studies reported that 64.8–85.3% of hemorrhagic MMD patients could achieve satisfactory neoangiogenesis (Matsushima Level A, B) after direct/combined bypass [ 12 , 13 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative color-coded parametric DSA (QDSA, Syngo iFlow) is an emerging DSA technique which provides objective perfusion parameters like time-to-peak (TTP), mean transit time (MTT), and ratios of area under the curve (AUC ratio) to assess hemodynamic changes of a certain artery after bypass surgery. Although it does not provide information on cerebral parenchyma perfusion, it is useful for measuring blood supply from the internal and external carotid artery systems [8,9]. However, DSA is not recommended for pediatric patients or patients in poor conditions, due to its invasiveness, time consumption, and need for anesthesia.…”
Section: Digital Subtraction Angiography (Dsa)mentioning
confidence: 99%